2022
DOI: 10.1007/s00127-022-02233-x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical mode of delivery and behavioural outcomes in childhood and adolescence: findings from the Millennium Cohort Study

Abstract: Purpose To examine the association between mode of delivery (in particular caesarean section) and behavioural outcomes in offspring at six time-points between age 3 and 17 years. Methods Similar to previous work examining the association between mode of delivery and behavioural outcomes in offspring at age 7, we used maternal-reported data from the Millennium Cohort Study. Data on mode of delivery were collected when children were 9 months and categorised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Our findings are broadly consistent with few existing studies that have reported no significant association between mode of delivery and child behavioural problems [ 31 34 ]. In the UK Millennium cohort study, Curran et al [ 31 ] found no association between modes of delivery and behavioural difficulties (also measured by SDQ) in children aged 7 years.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are broadly consistent with few existing studies that have reported no significant association between mode of delivery and child behavioural problems [ 31 34 ]. In the UK Millennium cohort study, Curran et al [ 31 ] found no association between modes of delivery and behavioural difficulties (also measured by SDQ) in children aged 7 years.…”
Section: Discussionsupporting
confidence: 93%
“…This study also used CBCL to measure children internalising problems and did not report findings from the CBCL sub-scales. However, more comparable studies by Maher et al [ 34 ] and Leung et al [ 33 ] found no evidence of associations between assisted vaginal delivery and emotional problems at age 11 when measured by SDQ. Taken together, the overall evidence signals the need for further research, particularly in older children, to confirm the robustness of our findings as well as to better understand the relationship between assisted vaginal delivery and offspring emotional development.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research, although limited, identifies emergency C-sections as an influential factor in the development of childhood behavioral problems [3,50]. Emergency C-sections are associated with higher total SDQ and peer problem scores among five-year-old children [50]. The findings of a study performed by Rutayisire, Wu [3] also support this link; however, it identified an association between elective and emergency C-sections and total abnormal SDQ scores among children aged three to six.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research, although limited, identifies emergency C-sections as an influential factor in the development of childhood behavioral problems [3,50]. Emergency C-sections are associated with higher total SDQ and peer problem scores among five-year-old children [50].…”
Section: Discussionmentioning
confidence: 98%